Ekstraksi Pektin dari Limbah Kulit Jeruk (Citrus sinensis) dengan Metode Ekstraksi Gelombang Ultrasonik Menggunakan Pelarut Asam Klorida (HCl) - Ariska Damanik, Delvia; Pandia, Setiaty (Jurnal Teknik Kimia USU, 2019)
Pectin is complex polysaccharide contained D-galacturonic acid bonded by Î± -1,4 glucosidic in plant cell walls. Pectin widely used in pharmaceutical, food and beverage industries. This study evaluates the effect of solvent and stirring speed on pectin characteristic. The study utilizes ultrasonic wave and acid solvent at the presence of ethanol to yield pectin following by drying to obtain dried pectin. This study carries out using 25 grams orange peels, 10 %, chloride acid solvent, 60 minutes extraction time, temperature of 60 oC, ultrasonic wave speed 50 KHz and 16 hours settling time at various solvent concentrations 0.025 N; 0.05 N; 0.075 N and stirring speed 0 rpm; 50 rpm; 100 rpm; 150 rpm. The results showed that the highest yield of pectin extraction was obtained at concentration of 0.075 N with 20.12 %; stirring speed 150 rpm, water content 8.0 %; 4,0 % ash content, and 7.44 % methoxyl content.